Interpersonal Relations Orientation And Leadership Styles Of Malaysian Managers: Relationship And Impact Of Demograpidc Variables - V.Odayappan, Selvaraj (Universiti Sains Malaysia, 2000)
This research attempts study the relationship between interpersonal relations orientation which is also known as interpersonal style and the leadership styles adopted by Malaysian managers. It also seeks to examine the impact of demographic variables between these two styles. The interpersonal relations orientation in this study comprises aggressive, submissive and assertive behavior and the leadership style measures telling, selling, participating and delegating leadership styles.